Effects of Resistance Band Exercise on Vascular Activity and Fitness in Older Adults - Smith, Mark F.; Ellmore, Mistrelle; Middleton, Geoff; Murgatroyd, Paul M.; Gee, Thomas I. (International Journal of Sports Medicine, 2017)
This study investigated the effects of a low to moderately intense resistance-band exercise intervention on cutaneous microvascular function in an older population. 18 sedentary healthy participants (age: 58±5) were assessed for their upper and lower-limb endothelial cutaneous vascular conductance using laser Doppler fluximetry with endothelial-dependent (80 μl acetylcholine chloride), and -independent vasodilation (80 μl sodium nitroprusside). In addition, participants underwent a range of functional assessments (cardiopulmonary fitness, strength, flexibility), and completed a perceived quality of life questionnaire. Participants were randomised into 2 groups: Exercise (EX) and Control (CON), and followed either an 8-week self-supervised home-based resistance-band intervention or maintained their habitual lifestyle. Following post-intervention assessment (n=16; EX=7, CON=9), EX improved acetylcholine-chloride-mediated endothelial-dependent vasodilation within the lower limb (cutaneous vascular conductance at 2 000 μCb; P<0.01), but without associated changes in the upper limb. Exercise, compared to CON, significantly affected sodium-nitroprusside-mediated independent vasodilation in the upper limb (P<0.01) at 2 000 μCb, but without associated changes in the lower limb. Of functional assessments, only lower limb strength and flexibility improved for EX (P<0.05). EX experienced positive changes within global measures of General Health, Bodily Pain and Energy/Fatigue (P<0.05). An 8-week home-based resistance-band exercise programme improves age-provoked microcirculatory endothelial vasodilation, but without concomitant changes in cardiopulmonary and anthropometric measures.
Keywords: microcirculation; fitness assessment; resistance training; endothelium; ageing